2019
DOI: 10.1021/acssuschemeng.9b00699
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous/Vanadium Sites on MIL-101 for Selective CO Adsorption from Gas Mixtures with Superior Stability

Abstract: For practical applications Cu­(I) π-complexation adsorption demands both a high performance and a good stability. In this work, we simultaneously incorporated copper and vanadium into a typical metal–organic framework (MOF) of MIL-101. Thanks to the assistance of V, selective reduction of Cu­(II) to Cu­(I) was efficiently realized at a low temperature of 250 °C. Compared with the common reduction temperature of over 450 °C, the temperature in this work was dramatically reduced. The low temperature can guarante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Also, the values of ΔG sol and ΔS sol were – 219.2 J mol −1 and − 63.6 J mol −1 K −1 at 353.2 K, respectively. Thereby, the value of Δ H sol for [BimH]Cl‐CuCl‐1.0ZnCl 2 was little more than the hydrogen bonding energy range from −10 to −20 kJ mol −1 , 35,36 again confirming the physical absorption of CO in the DES [BimH]Cl‐CuCl‐1.0ZnCl 2 .…”
Section: Resultsmentioning
confidence: 78%
“…Also, the values of ΔG sol and ΔS sol were – 219.2 J mol −1 and − 63.6 J mol −1 K −1 at 353.2 K, respectively. Thereby, the value of Δ H sol for [BimH]Cl‐CuCl‐1.0ZnCl 2 was little more than the hydrogen bonding energy range from −10 to −20 kJ mol −1 , 35,36 again confirming the physical absorption of CO in the DES [BimH]Cl‐CuCl‐1.0ZnCl 2 .…”
Section: Resultsmentioning
confidence: 78%
“…ILs, ionic liquids ratio of CO and N 2 on various ILs and adsorbent materials at 1 bar was further compared, and the results are presented in Figure 3. It is demonstrated that the CO/N 2 absorption amount ratio for [EimH][OAc]-0.6CuOAc reached a record value of 967 at 293.15 K and 1 bar, which is much higher than many ILs[12][13][14]20,27 and most porous MOFs adsorbent materials [29][30][31][32]. The ultralow N 2 capacity plus superior CO uptake in [EimH][OAc]-0.6CuOAc contributes to the highest CO/N 2 ideal separation selectivity.…”
mentioning
confidence: 98%
“…MIL-101­(Cr) was prepared based on a typical route. , First, Cr­(NO 3 ) 3 ·9H 2 O (2.0007 g), TPA (0.8307 g), and ultrapure water (25.2 mL) were mixed and stirred for 1 h. Then, HF (0.8 mL) was added into the mixture. Additional 2 h of stirring was conducted; after that, the mixture was loaded into a Teflon-lined stainless-steel autoclave and followed by being treated at 220 °C for 8 h. Then, the product was gradually cooled down to 25 °C, filtrated, and dried at 150 °C.…”
Section: Methodsmentioning
confidence: 99%